Предмет:
МатематикаАвтор:
аноним²Разложим выражения на множители:
а) a² + a * d - a - d = (a² + a * d) - (a + d) = a * (a + d) - (a + d) = (a + d) * (a - 1);
в) 3 * a * b - b² + 3 * a² - a * b = (3 * a * b - b²) + (3 * a² - a * b) = b * (3 * a - b) + a * (3 * a - b) = (3 * a - b) * (b + a);
д) b² * c² + c³ - b³ - b * c = c² * (b² + c) - b * (b² + c) = (b² + c) * (c² - b);
Разложим на множители:
а) a * x - a + b * x - b + c * x - c = a * (x - 1) + b * (x - 1) + c * (x - 1) = (x - 1) * (a + b + c);
в) a * x - b * x - x + a * y - b * y - y = x * (a - b - 1) + y * (a - b - 1) = (a - b - 1) * (x - y);
д) a⁵ - a⁴ * b + a³ * b² - a² * b³ + a * b⁴ - b⁵ = a⁴ * (a - b) + a² * b² * (a - b) + b⁴ * (a - b) = (a - b) * (a⁴ + a² * b² + b⁴).
Автор:
binkybutlerДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть